Critical success factors for corporate social responsibility adoption in the Malaysian construction sector: a delphi study - Anat Anaqie, Zahidy (2021)
The fact that construction sector was plagued with a broad variety of unethical practices has called for the urgent need to promote an ethical business philosophy in line with the concept of corporate social responsibility (CSR). However, understanding the concept of CSR in this sector and how to practice it, is limited. This study aims to explore the critical success factors (CSFs) for CSR adoption in the Malaysian construction sector. Two research approaches were adopted including a Delphi technique and a case study. A threeround Delphi technique was used to identify and rank the top most CSFs. A panel of sixteen construction sector experts was formed to participate in the study. A list of twelve potential factors was extracted from literature and included in Delphi Round 1 questionnaire. In Delphi Round 1 brainstorming process, eleven factors have achieved consensus as selected for more than 50% by the experts. In addition, four new factors suggested by the experts were accepted. As a result, fifteen factors emerged from this round were included in Delphi Round 2 questionnaire. In the ranking process of Delphi Round 2, consensus as measured by Kendall’s W value was found to be 0.398, indicated a weak agreement among experts and the need for another Delphi round. In Delphi Round 3 controlled feedback process, Kendall’s W value increased to 0.784 which implied a strong consensus was reached. The results showed that successful adoption of CSR depends on eight CSFs: financial resources, top management support, managerial or internal CSR skills, national economic growth, employees’ education and training on CSR, the participation of key stakeholders in CSR process, effective CSR communication, and organisational structure. Level of readiness of the Malaysian construction firms to adopt CSR was measured against the validated CSFs. A series of interviews was conducted with five respondents from five local construction firms concerning their current CSR practice. It was noticed that the firms had already entirely or partially practiced the eight CSFs. It would be safe to conclude that the Malaysian construction firms are ready to adopt CSR into practice. Nonetheless, they need to improve their practice on the established CSFs to gain maximum results from CSR adoption. This study highlighted that CSR framework could be useful as the platform for advanced mitigation strategies to improve the construction sector’s image and also as a strategic competitive tool for the firms to remain sustainable in business. Finally, policymakers could also consider the findings when promoting CSR agenda or development programs in the Malaysian construction sectors.